Preliminary thoughts on auditing the efficiency of a physiotherapy service using a computer programme - M. J. Runnalls (AOSIS, 1980)
The initiation of a documentation audit of the efficiency of physiotherapy services provided in a large general teaching hospital is discussed. Results and trends of behaviour as analysed by computer programmes are shown.